1998
DOI: 10.1590/s0066-782x1998000500005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de dislipidemias na demanda laboratorial de três diferentes prestadores de assistência

Abstract: The best lypid profile observed in subjects from SUS suggests social differences in the prevalence of dyslipidemias. As compared to other dyslipidemias, HDL-c < 35mg/dL prevalence was lower than expected in all three groups. The data may provide insights to medical doctors and other health care professionals regarding the questions of dyslipidemias. It can also provide objective information to the patients and encourage them to change their life styles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
5
0
3
Order By: Relevance
“…The rates of hypercholesterolemia and hypertriglyceridemia found in this study (around 30%) are similar to results reported from other studies carried out in the Brazilian population showing rates of 20% for hypercholesterolemia 39 and 30% in the case of hypertriglyceridemia 40 in women over 50 years of age. Data from the US National Health and Nutrition Examination Surveys (NHANES) show Physical activity and parameters of physical fitness Da Silva et al…”
Section: Discussionsupporting
confidence: 91%
“…The rates of hypercholesterolemia and hypertriglyceridemia found in this study (around 30%) are similar to results reported from other studies carried out in the Brazilian population showing rates of 20% for hypercholesterolemia 39 and 30% in the case of hypertriglyceridemia 40 in women over 50 years of age. Data from the US National Health and Nutrition Examination Surveys (NHANES) show Physical activity and parameters of physical fitness Da Silva et al…”
Section: Discussionsupporting
confidence: 91%
“…Within this group of patients, 118 (79.7%) had normal LDL levels and 30 (20.3%) exhibited LDL ≥ 160 mg/dL. Compared to the historical reference value for hypercholesterolemia prevalence among the Brazilian population,13 statistical analysis showed no difference in frequency between the two proportions (p  =  0.1087, chi‐square).…”
Section: Resultsmentioning
confidence: 75%
“…To homogenize our sample with that used in the Brazilian survey13, taking into account age data, we considered only SHL patients aged more than 20 years. Within this group of patients, 118 (79.7%) had normal LDL levels and 30 (20.3%) exhibited LDL ≥ 160 mg/dL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations